ANALISA KARAKTERISTIK KEUNGGULAN ETHANOL SEBAGAI SUMBER ENERGI ALTERNATIF PADA SEKTOR TRANSPORTASI - Suarna, Endang (Badan Pengkajian dan Penerapan Teknologi, 2012)
As the energy consumption continues to increase, while, the most of the energy consumption is met from oil, and the oil supply is going to limited; energy diversification is needed. Ethanol can be used as an option for the energy diversification. Ethanol is a renewable energy and environmentally friendly fuel which used as an energy alternative in the transportation sector can reduce the gasoline consumption. As gasoline is one of subsidized fuels and imported fuel, reducing gasoline consumption has also impact on reducing oil subsidy and import. As the ethanol has lower greenhouse gas of CO2, and pollutant emissions of CO, NOx, SO2, and particulate matters, ethanol utilization for energy is safe for human health and environment. Ethanol also has higher octane number and oxygen content that lead to better performance of the fuel and vehicle. Ethanol fuel program is also more creating job opportunities.